Making the Moment Matter Care Theory for Teacher Learning - Trout, Muffet; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
(3z(BMaking the Moment Matter is a wonderful contribution to the literature on meaningful teacher education. Grounded in Nel Noddings$1 (Brelational ethic of care, this finely written book explores both the moral foundations and the lived realities of facilitating teacher development through pedagogical caring. Trout$1 (Bs theoretically rich, carefully designed, and engaging inquiry could not be more timely. In an era when reform talk in teaching and teacher education is increasingly characterized by reference to outcomes, accountability and (3z(Bvalue added(3y (Bmeasures, this book reminds us that better teaching is a process centered on caring relationships. Her work has a great deal to offer many different readers$1 (Beducational researchers interested in models of well-crafted studies of practice, teacher educators looking for insights into the complex work of teacher development, and others who wish to learn more about the manner of relationships that stand at the heart of education.(3ys
Keywords: Education; Education; Education (general).